SAFETY AND EFFICACY OF EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY VERSUS PERCUTANEOUS NEPHROLITHOTOMY FOR THE TREATMENT OF MODERET SIZE KIDNEY STONES IN THE MIDDLE AND UPPER POLE - Stojanoski, Ivica; Krstev, Toni; Stavridis, Sotir; Glavinov, Maja Sofronievska; Calcevska, Slavica; Beaka, Gordana Bozinovska (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction: Given the high incidence and recurrence of nephrolithiasis, technological advances have been made to dramatically improve minimally invasive techniques for treatment of kidney stone, such as extracorporeal shock wave lithotripsy (SWL) and percutaneous nephrolithotomy (PCNL). SWL is the standard method in the treatment of kidney stones smaller than 10 mm while PCNL methods of choice in the treatment of kidney stones larger than 20 mm. But for the choice of method for the treatment of 10 to 20 mm, upper and middle calices stones still there are conflicting opinions.  Objectives: The aim of the study was to evaluate the efficacy and safety of  SWL and PCNL in the treatment of 10-20 mm kidney stonei in the middle and upper  pole and to choose the optimal procedure.  Material and methods: The clinical study was designed as a randomized prospective study and conducted in GH "8th of September" - Skopje in the period from December 2023 to Januar 2025. During the study for both methods were analysed success rate, rate of re-treatment, the need for additional procedures, the degree of complications and the duration of the intervention and the hospital stay.  Results: The study included 81 patients randomized into two groups. The first group included 41 patients treated with SWL, and the second group included 40 patients treated with PCNL. SWL vs. PCNL success rate was 90% vs. 82.9% (p = 0.29); the rate of re-treatment of SWL was 39.02% versus 0% of PCNL. (p = 0.00001). The additional procedures were equally present in the two treatment groups 14.64% in SWL and 15% in PCNL (p = 0.96). PCNL was associated with a significantly longer duration of treatment versus SWL, 110.2 ± 17.7  minutes versus 47.1 ± 3.3 minutes respectively (p = 0.00000). Complications were less frequently detected in patients treated with SWL compared to patients treated with PCNL, 17.1% versus 32.5% respectively. (p = 0.11) The mean length of hospital stay was significantly shorter in patients treated with SWL compared to PCNL, 1.1 ± 0.4 versus 6.0 ± 1.7 days (p <0.0001).  Conclusion : This study shows that PCNL and up to three SWL treatments are safe and comparatively effective in treating patients with stones in the upper and middle calices ranging 10–20 mm. Key words: urolithiasis, nephrolithiasis, extracorporeal lithotripsy, percutaneous nephrolithotomy, kidney.